2020
DOI: 10.1016/j.dcn.2020.100782
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on structure of the social brain in childhood

Abstract: Prosocial behavior and empathy are important aspects of developing social relations in childhood. Prior studies showed protracted structural development of social brain regions associated with prosocial behavior. However, it remains unknown how structure of the social brain is influenced by genetic or environmental factors, and whether overlapping heritability factors explain covariance in structure of the social brain and behavior. The current study examined this hypothesis in a twin sample (aged 7–9-year; N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 94 publications
4
24
0
Order By: Relevance
“…, 2019 ). The relatively similar development of the precuneus across persons is consistent with recent findings from a twin study that showed that the structure of the precuneus is particularly genetically driven and less sensitive to environmental influences ( van der Meulen et al. , 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…, 2019 ). The relatively similar development of the precuneus across persons is consistent with recent findings from a twin study that showed that the structure of the precuneus is particularly genetically driven and less sensitive to environmental influences ( van der Meulen et al. , 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…For three of our four social brain regions of interest (ROIs: mPFC, TPJ and pSTS), we used the same templates as used and described in full detail by Mills et al. (2014) and van der Meulen et al. (2020) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, heritability of white matter tracks was observed in twin studies including neonates, 1-year-olds, and 2-year-olds, but no evidence for heritability of white matter change between the age of 1 and 2 years ( Lee et al, 2019 ). In older children and adolescents, heritability estimates are much higher ( van Soelen et al, 2012 ) but genetic influence differs between regions in the brain, with more pronounced environmental influences in the social brain network than in visual and motor cortex ( Van der Meulen et al, 2020 ). Understanding the genetic and/or environmental contributions and the changes in their impact across development may reveal potential windows of sensitivity to the environment during development.…”
Section: Differential Susceptibility To Social Experiencesmentioning
confidence: 99%